Texts and Co-texts of Digital Native Elementary School Art Learning during the Covid-19 Pandemic - Pance Mariati; Sri Hartatik; Suharmono Kasiyun; Ratih Asmarani (Universitas Kanjuruhan Malang, 2021)
This study aims to explain the synthesis of conceptual changes in art learning for digital natives students to reflect current art learning practices so that they become a foothold in future improvement. This research uses a case study approach to art learning for digital natives students in 3 elementary schools in Pacitan, East Java, from May 2020 to May 2021 with 100 students and 50 teacher. This research discusses material and formal objects in learning art into text and co-text as a perspective from educational semiotics classroom, which is an effort to systematize based on the elements of art learning for digital natives. The results showed that the elements of art learning, such as the learning model, the intimacy aspect between teachers and students, and the digital natives learning ecosystem in them are continuously developing by considering the element of entrainment. Integration between learning elements is needed to meet the prerequisites for resilience for digital natives students, including intimacy between text and co-text learning, text competence and co-text learning, and entrainment in a learning-based ecosystem of digital natives class.